Performance analysis of high‐power three‐phase current source inverters in photovoltaic applications - Payam Alemi; Jiacheng Wang; Jianwen Zhang; Sahar Amini (IET Circuits, Devices and Systems)
Abstract In this study, a design of a medium‐voltage current source inverter (CSI) and a conventional voltage source inverter (VSI) is presented for high‐power (1 MW) photovoltaic (PV) applications. The characteristics of a new 1700 V/1600 A reverse‐blocking insulated‐gate bipolar transistor (IGBT) in the CSI are compared with the same generation of IGBT device in the VSI. The passive components design, including ac‐ and dc‐side filters, are developed based on a given design procedure. Power loss analysis is demonstrated to compare the CSI efficiency with the VSI's in the specified power range. Simulation and experimental results for the operation and control of the CSI in grid‐connected PV application in the central power range show the effectiveness of the proposed CSI and the possibility of applying it as a viable topological candidate.